A Study on Spiritual Quotient Among College Students In Coastal Town of Mangalore, Karnataka State. (International Journal of Scientific Research and Management (IJSRM), 2015)
The present study aims to assess the spiritual quotient of college students in Mangalore City. Two collegewere selected by simple random sampling. About 100 students were selected from each of the colleges takenup for the study. Majority of the students fall in average SQ category (83.88% ). 21.1 % of students fall inhigh category. Medical students had a statistically significant higher mean score compared to that of thedegree college students . Mean SQ of the female students was more than males and it was statisticallysignificant. Jain and sikh students had a better score. In the self improvement test where situations werepresented before students, Christians scored highest (72.86%).